mRNA vaccine politics: responsible governance coordination for vaccine innovation in times of urgency - Katerina Sideri (Journal of Responsible Innovation)
COVID-19 crisis reaffirmed the power of a few companies to scale up production for mRNA vaccines, which created injustice as a few nations in the developed world benefited first from available vaccines, while LMICs waited at the back of the queue. Initiatives such as the South Africa mRNA tech transfer hub sought to address these concerns. The article engages in an analysis of the different visions that underpin the current vaccine innovation system and the South Africa tech transfer hub. I argue that the dominant vision of global scalability by pharmaceutical companies which are ‘too big to fail’ limits the transformative potential of the hub and I propose ways in which responsible governance coordination can address some of the failings of the system.